PENERAPAN METODE ROLE-PLAY SEBAGAI "TOUR GUIDE" CILIK BERBASIS PARIWISATA WONOSOBO UNTUK MENINGKATKAN KETERAMPILAN BERBICARA (SPEAKING) BAHASA INGGRIS SISWA SD/MI - Mustaqim, Alfri Khoerul Mustaqim; Roni Muslikah; Indra Pratama; Astya Silvina Afra; Arfiyan Nasiha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of students in the IPAS subject, particularly on the topic of matter and its changes, as well as the lack of supplementary teaching materials that support students’ active involvement in the learning process. This study aimed to develop a Discovery Learning-based IPAS Student Worksheet (LKPD) that is valid, effective, and attractive for fourth-grade students at UPTD SDN Banyuajuh 2. This research employed the Research and Development (R&D) method using the 4D development model, which consists of four stages: define, design, develop, and disseminate. The research subjects included expert validators, a fourth-grade teacher, and fourth-grade students of UPTD SDN Banyuajuh 2. Data were collected through interviews, observations, questionnaires, and tests. Data analysis was conducted to determine the validity, effectiveness, and attractiveness of the developed product.The results showed that the Discovery Learning-based IPAS Student Worksheet met the criteria of being highly valid, effective, and highly attractive. The validation results indicated percentages of 86% from the material expert, 90% from the instructional design expert, and 93% from the teaching material expert, all categorized as highly valid. The effectiveness of the product was demonstrated through the results of teacher and student activity observations in the limited trial, which reached 95% and 97%, respectively, with a classical mastery level of 100%. In the implementation stage, student activity reached 94%, and classical mastery reached 96%. The attractiveness of the product was demonstrated by the student response questionnaire result of 94%, both categorized as highly attractive. Based on these findings, the Discovery Learning-based IPAS Student Worksheet on matter and its changes is feasible to be used as a teaching material in IPAS learning at the elementary school level